“Implantación de Contabilidad de Costos por Ordenes de Producción y Análisis Financiero a la Imprenta “Offset Copycom” Periodo Enero a Marzo del 2012 - Japón Hurtado, Byron Bladimir (2016)
The thesis entitled “IMPLEMENTATION OF COST ACCOUNTING FOR ORDERS PRODUCTION AND FINANCIAL TO PRINT ANALYSIS "OFFSET COPYCOM " PERIOD JANUARY TO MARCH 2012” was made by the general purpose of designing and implementing an accounting system cost to get to know actual data of the company through the financial statements and financial analysis, thus contributing to taking corrective measures in the medium and long term. The proposed objectives were carried out; starting with the development of a complete chart of accounts and detailed accounting information that serves as the press , also through the implementation of the accounting system for production orders could determine the costs of manufacturing products printing; during the same relevant documents that will enable proper control was developed ; and the application of analysis and financial indicators which allow the business owner to know the economic and financial information of it. The methodology used was to request relevant information about buying and selling invoices corresponding to the period established for the purpose; costs 5 incurred, values of salaries to workers and other economic data that are directly linked to the object of study and provide real data that facilitated their situation at the end of the accounting cycle. Among the key findings it highlighted that the company needs to know the real unit costs of products to determine the selling price, the same will be according to the local economy and especially that of competition in the market. Against this is recommended to take into account the suggestions made in a timely manner, since they are designed to contribute significantly to the management undertaken by its owner from the start of production activities